2021
DOI: 10.1177/10775587211013628
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Quality of SK&A’s Office-Based Physician Database for Identifying Oncologists

Abstract: Health services research increasingly uses commercial databases that capture provider practice characteristics. Little is known about how these data sets compare along other dimensions with publicly available data. We assess the quality of one of the most commonly used commercial databases, SK&A’s office-based physician database, for capturing oncologists who bill the Medicare fee-for-service program. Using 2017 data, we find that nearly 74% of the oncologists in Medicare claims can be found in the SK&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Data on oncologists were obtained from the health information company IQVIA. IQVIA’s OneKey (previously SK&A) is an annual compilation of office-based physicians practicing in the US and is estimated to include 74% of oncologists billing Medicare fee-for-service and 90% of physicians across all specialties . As described elsewhere, we linked physician and practice data to annual data on pharmacies using organizational names and locations to identify oncologists and oncology practices that opened and operated on-site pharmacies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data on oncologists were obtained from the health information company IQVIA. IQVIA’s OneKey (previously SK&A) is an annual compilation of office-based physicians practicing in the US and is estimated to include 74% of oncologists billing Medicare fee-for-service and 90% of physicians across all specialties . As described elsewhere, we linked physician and practice data to annual data on pharmacies using organizational names and locations to identify oncologists and oncology practices that opened and operated on-site pharmacies.…”
Section: Methodsmentioning
confidence: 99%
“…IQVIA's OneKey (previously SK&A) is an annual compilation of office-based physicians practicing in the US and is estimated to include 74% of oncologists billing Medicare fee-for-service and 90% of physicians across all specialties. [10][11][12] As described elsewhere, 1 we linked physician and practice data to annual data on pharmacies using organizational names and locations to identify oncologists and oncology practices that opened and operated on-site pharmacies. Annual data on pharmacies were obtained from the National Council for Prescription Drug Programs, a nonprofit organization that collects registration information on a wide range of pharmacies, including chain and independent retail pharmacies, clinic pharmacies, and nonpharmacy dispensing sites (eg, in-office sites).…”
Section: Datamentioning
confidence: 99%
“…8 OneKey is an annually compiled file of office-based physicians estimated to cover 74% of oncologists billing Medicare feefor-service and 90% of physicians across all specialties. [8][9][10] OneKey includes physician names, specialties, practice names, practice site addresses, daily patient volume, medical group affiliations, and hospital and health system affiliations. Because OneKey has been reported to understate practices' hospital affiliations, 11 we augmented these data with information from web searches on practices' hospital and health system (ownership) affiliations and, for 2016 and 2018, publicly available vertical integration data from the Agency for Healthcare Research and Quality Comparative Health System Performance Initiative Compendium of US Health Systems.…”
Section: Data and Study Populationmentioning
confidence: 99%
“…Studies of the completeness of the SK&A data set have found it to provide reasonably accurate up-to-date address and ownership information of physicians. [21][22][23] Provider Utilization and Payment…”
Section: Integrated Physiciansmentioning
confidence: 99%